Protection of socio-biodiversity in territorial planning and manegement instruments: the case of the butia palm groves of Imbituba (SC) (PerCursos, 2025)
Butia palm groves are ecosystems where palm trees of the genus Butia predominate. The south-central coast of Santa Catarina and the northern region of Rio Grande do Sul are home to the species Butia catarinensis, which is considered endemic and threatened with extinction. Butia palm groves have historically been managed and utilized by local communities and are products of socio-biodiversity. The aim of this study was to identify the main threats to Butia palm groves and to analyze their conservation within Imbituba's legal provisions and territorial planning instruments. The methodology included a participatory mapping workshop of the areas where Butia palm groves are present and have been suppressed, an analysis of legislation and territorial planning instruments, and interviews with representatives of the local community, institutions involved in the Butia palm grove issue, and the municipal government. Urban and industrial growth was identified as the main threat to Butia ecosystems, and despite the existence of legal protection provisions, these are often neglected in territorial planning and management.
Keywords: sociobiodiversity; butia catarinensis; territorial planning; nature conservation; restinga